The Perception of Senior High School Students in Banyumas District towards Profession and Education of Nursing Bachelor - Handoyo,; Kamaluddin, Ridlwan; Ekowati, Wahyu (Jurusan Keperawatan FIKES UNSOED, 2006)
The profession of Nursing has declared it's self as an independent profession in National nursing Workshop in 1983. Nursing profession nowadays is still in the process of professionalism. One effort to support the professionalism of nursing is by carried out a bachelor degree of nursing in universities. The student of senior high school as a row input of bachelor degree ofÃ‚Â nurse,Ã‚Â probably hasÃ‚Â particularÃ‚Â perception about profession and education of nursingÃ‚Â bachelor. The Purpose of this research was to find out a description aboutÃ‚Â perceptionÃ‚Â of senior high school students in third grade towards profession and education of nursingÃ‚Â bachelor. This research was using a descriptive method. Populations of research were all students of senior high school third grade inÃ‚Â banyumasÃ‚Â district,Ã‚Â annualÃ‚Â period of 2005 / 2006. Samples were taken by grade random samplingÃ‚Â accordingÃ‚Â groups proportionally.Ã‚Â InstrumentÃ‚Â that used to measure the perception was aÃ‚Â stucturedÃ‚Â questionnaire with Likert scale. The instrument was tested for itÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s reliability and validity.Ã‚Â QuestionnaireÃ‚Â composedÃ‚Â withÃ‚Â 11 items covering the matter of nursing profession, and 4 items forÃ‚Â educationÃ‚Â of nursingÃ‚Â bachelor. The answer of eachÃ‚Â itemsÃ‚Â furthermoreÃ‚Â being counted withÃ‚Â percentage. Each score was divided with the highest score, then the percentage of each item was consulted with evaluation category by Arikunto (1996). The Result of this research showed that the perception of senior high school students inÃ‚Â banyumasÃ‚Â district towardsÃ‚Â professionÃ‚Â ofÃ‚Â nurse,Ã‚Â was enough (70,7%). Meanwhile, the perception towardsÃ‚Â educationÃ‚Â of nursingÃ‚Â bachelorÃ‚Â was either enough (71,8%). The conclusion was that the perception of senior high school at third grade inÃ‚Â yogyakartaÃ‚Â district annual period 2005 / 2006 was good enough.